Vital Space in the House of Buendía - Nina M. Scott (Studies in 20th & 21st Century Literature, 1984)
In terms of both narrative and thematic organization, Gabriel Garcia Márquez's One Hundred Years of Solitude deals with tightly-closed structures. Whereas from the beginning Macondo has been interpreted in a variety of ways, critics have paid less attention to the meaning of the Buendía house itself. A close reading of the text shows that the way in which certain characters interact with the physical spaces of the house is highly symbolic and closely related to the thematic development of the entire novel. The rise and fall of the Buendía dynasty is presided over by three women, who function as the rulers of the house: Ursula, Fernanda and Amaranta Ursula. Each one of them affects the architecture of the structure, but as the house increasingly has a life of its own, is in turn shaped by the dwelling itself. The fall of the Buendía family is reflected in the loss of control not only of the lives of certain characters, but of the vital spaces within the house that they inhabit.
Keywords: Gabriel García Márquez; Colombian Literature; One Hundred Years of Solitude; structures; Buendía house; physical spaces; symbolism; Buendía dynasty; women; dwelling; dwelling space; control; loss; vital space